DETERMINATION OF DIAGNOSTIC SIGNIFICANCE OF WRIST CIRCUMETRIC SIGN IN SIDDHA SYSTEM OF MEDICINE (International Journal of Ayurveda and Pharma Research, 2017)
Aim: Determination of diagnostic significance of wrist circumetric sign in siddha system of medicine.Materials and methods: Patients are randomly selected between the age 13years to 70 years with selected diagnoses like Madhumegam, Athikuruthiazhutham (Hypertension), Thamaraganoi, Putrunoi, Kalanjagapadai (Psoriasis), Moolam, Powthiram (Perianal fistula), Vali azhal keel vayu, Pakkavatham, Karupaisathaikatti (Uterine fibroids).Results and observation: Most of the patients MKN values fell within the range of 9-9¾ fb. This range of 9-9¾ fb MKN, was observed in Athikuruthiazhutham, Putrunoi, Moolam, Powthiram, Thamaraganoi, Madhumegam, Pakkavatham, healthy volunteers. 8-8¾fb MKN range was observed in 41.5% of Kalanjagapadai and vali azhal keel vayu cases. 10 - 10¾fb was observed in 43.1 % of patients with Karuppaisathaikattigal (Uterine fibroids).Conclusion: Since all other diseases had non-specific Manikkadai nool range except the condition Karupaisathaikattigal (uterine fibroid), Manikkadai nool can be used to assess screening test in detecting the presence of uterine fibroids and cardiac diseases according to this study.